Theft Detection System Using Laser Based on Arduino Uno - Riyadhul Fajri; Zulkifli Zulkifli; Denny Prananda (Universitas Malikussaleh, 2026)
The increasing number of theft cases demands an effective, simple, and affordable security system. This research aims to design and implement an Arduino Uno-based burglar detection system utilizing laser light as a detection medium. This system works based on the principle of breaking the laser light directed to a Light Dependent Resistor (LDR) receiver sensor. When the laser light is blocked by an object, a change in light intensity occurs which is then processed by the Arduino Uno to activate an alarm as an indicator of interference. The research methods used include hardware and software design, system assembly, and tool performance testing. The test results show that the system is able to detect interference in real-time with a fast response and a good level of reliability. In addition, this system has advantages in terms of economical costs, ease of implementation, and flexibility for further development, such as integration with an Internet of Things (IoT)-based notification system. Based on the design and testing results, the Arduino Uno-based burglar detection system using a laser sensor can work well in detecting interference. The system is able to respond quickly when the laser light is broken by activating an alarm as a warning sign. From the test results, it can be concluded that this tool has a fairly good level of reliability, is easy to design, and has a relatively low cost. In addition, this system is also flexible and can be further developed by adding features such as remote notification or integration with IoT technology. Thus, this system can be used as an alternative solution to improve environmental security simply, effectively, and efficiently. In the future, the use of more sensitive and stable sensors, such as photodiodes or infrared sensors, can be considered to improve detection accuracy. As well as the addition of backup power sources (batteries or UPS) so that the system continues to function during power outages. With the presence of a laser that will control home security when residents are not at home and become more comfortable when left alone. Home residents through this tool system will be able to know the motion data between the sensor and objects that become obstacles. The status of the movement is displayed through sound and its status is displayed by LED lights.